PENGEMBANGAN E-LKPD BERBASIS LITERASI SAINS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SDN LALADAN - agustin, ina; Muhammad Amrillah Aziz (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2024)
Critical thinking is a thinking ability that includes the ability to analyze, draw conclusions, interpret, explain, and self-regulate the thought process that is carried out which is really needed by someone in an effort to solve problems. One way to support and improve critical thinking skills is scientific literacy. Scientific literacy is the ability to use scientific knowledge, identify questions, draw conclusions based on evidence to understand and help make decisions regarding nature and the changes made to nature through human activities. Researchers conducted research entitled